The potential of the city of Araguaína – TO, to touristic receptivity considering the dynamics of its urban pattern - Sydow, Elisabeth; Silva , Paola; Sydow, Ursula (Seven Editora, 2023)
Touristic activity represents an important option as a social, economical and cultural motivator for a specific area. But consistent tourism cannot exist without the building of civility. Urban beauty and security should be seen as civility factors. The city of Araguaína – TO developed itself with no order, which contributed to its poor urban aesthetics. The city has a specific land use regulation but there is no government inspection to accomplish it. There are obstacles on the sideways that difficult pedestrian access making many of them walk on the streets risking their lives. The aim of this research was to understand the perception that the city’s inhabitants have of the accessibility to the walkways, their safety to the inhabitants and to the tourists. It was also verified if they know that there is a specific regulation that sets the use of the sideways. The method used in this research was developed in the qualitative dimension by bibliographic research intending theoretical consistency, as well as, quantitative form, through the questionnaires applied to the Araguaína’s population. DOI:https://doi.org/10.56238/sevened2023.006-086